Comparative analysis of archers’ shooting performance scores by gender - Muh Batistuta Fitoni Nuradila; Yudik Prasetyo; Heru Prasetyo; Okky Indera Pamungkas S; Hary Widodo; Oviesta Tasha Retyananda; Septian Resi Wibowo (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2026)
Empirical evidence regarding gender differences in archery shooting performance remains inconsistent. This study aims to compare shooting performance scores between male and female archers. A comparative cross-sectional design was employed, involving 35 archers consisting of 16 males and 19 females selected through total sampling. Shooting performance was assessed in a single testing session comprising 36 arrows. The data were analyzed using descriptive statistics, the Shapiro–Wilk test, Levene’s test, an independent-samples t-test, and Cohen’s d effect size. The results revealed no statistically significant difference in shooting performance scores between male and female archers, t(33) = −0.920, p = .364. The effect size was small (Cohen's d = 0.31), indicating only a minor practical difference between the two groups. These findings suggest that gender may not be a primary factor determining archery shooting performance. Therefore, coaching programs should place greater emphasis on athletes’ individual abilities and performance characteristics rather than relying solely on gender-based considerations.